A comprehensive analysis of trade based money laundering preventive measures in the EU - Sniedzītis, Valters (Riga Graduate School of Law, 2019)
This thesis concerns the research on applicability of trade based money laundering preventive measures in the European Union. With the growing concern of criminals who legitimize illicit funds through trade, it is important to research how the relevant authorities approach this issue by regulation. Subsequently, the author analyzed the technical compliance and effectiveness of these measures in Latvia, Finland and Czech Republic. The results of the thesis are that, firstly, trade based money laundering preventive measures are achieved by interpretation of certain the 40 recommendations of the Financial Action Task Force. Secondly, It was established that generally all the countries had effectiveness between moderate and substantial level regarding the preventive measures
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Money laundering; Financial law